ESTABILIDADE DE CULTIVARES DE MILHO NOS TESTES REGIONAIS DE VERÃO E SAFRINHA NO ESTADO DE SÃO PAULO - Sawazaki, Eduardo; Paterniani, Maria Elisa A. G. Zagatto; Galvão, João Carlos C.; Duarte, Aildson Pereira; Merege, Walter H.; Garcia, Lina Leme Cesário (REVISTA DE AGRICULTURA, 2015)
ESTABILIDADE DE CULTIVARES DE MILHO NOS TESTES REGIONAIS DE VERÃO E SAFRINHA NO ESTADO DE SÃO PAULO